TINJAUAN YURIDIS TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA ELEKTRONIK DALAM PUTUSAN PENGADILAN NEGERI BANGKINANG NOMOR 407/PID-SUS/2020 PENGADILAN NEGERI BANGKINANG - Fajri, Muhammad; Syahrial, Syahrial; Prayudi Saputra, Rian (Jurnal Pahlawan, 2022)
In the current era of globalization, especially in cyberspace social networks, it has brought about very radical changes in communication. When people are in it, they must have good and correct ethics in interacting with others, because as we see, many of them make mistakes in interacting that result in themselves being subject to criminal sanctions that are detrimental to themselves because they have defamed someone's good name. The formulation of the problem in this study is How is the application of Criminal Law to criminal acts of defamation through the Media in decision number 407 / PID-SUS / 2020 / PN.BKN and What is the basis for the Judge's considerations in decision number 407 / PID-SUS / 2020 / PN.BKN. The method used is normative juridical. The results of the first study are the application of law to criminal acts against perpetrators of criminal acts of defamation through electronic media. The second is the judge's consideration, especially in decision number 407/Pid-Sus/2020/pn.bkn, that the judge has considered the facts revealed in the trial and considered the level of consequences arising from the criminal act committed by the defendant, which in this case can be a consideration by the judge in deciding a criminal case that will be undergone by the defendant. Keywords: Defamation, Electronic Media